2015
DOI: 10.4236/ojgas.2015.57017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors for Cirrhosis Hospital in Abidjan (Côte d’Ivoire)

Abstract: Cirrhosis is the cause of a high rate of death in hospitals. The aim of this research was to estimate the incidence of mortality and identify the risk factors associated with cirrhosis patients in hospital in Côte d'Ivoire. Methodology: It is a retrospective study covering from January 1 st , 2002 to December 31 st , 2011 at Centre Hospitalier et Universitaire de Yopougon in Abidjan. We concerned the cirrhosis patients that have been followed at the hepatology and gastroenterology department. Survival was esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
4
4
1
Order By: Relevance
“…Viral hepatitis is the most common cause of cirrhosis in our study with a predominance of hepatitis B. These results are similar to those of Sehonou in Benin [14] and Yao Bathaix in Côte d'Ivoire [7] who recovered hepatitis B respectively in 30.8% and 76.04% of cases.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Viral hepatitis is the most common cause of cirrhosis in our study with a predominance of hepatitis B. These results are similar to those of Sehonou in Benin [14] and Yao Bathaix in Côte d'Ivoire [7] who recovered hepatitis B respectively in 30.8% and 76.04% of cases.…”
Section: Discussionsupporting
confidence: 90%
“…This is close to the results of Bossali in Pointe-Noire in Congo [5]. However, in the studies of Yao Bataix and Karoui [7] [12], the stage at diagnosis is relatively less advanced, mainly stage B of Child Pugh.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, there were 153 patients, in which the number of male patients was double that of female patients (66.7%; 33.3%). This finding is consistent with the previous studies in Vietnam [19,20] and others worldwide [21][22][23][24]. Thus, the male predominance is apparent, especially in developing countries.…”
Section: General Patient Characteristicssupporting
confidence: 93%
“…SBP was associated with female gender, leukocytosis and cloudy appearance of ascetic fluid [24]. Bathaix et al, in a series of 221 patients, in Ivory Coast, identified SBP as prognosis factor in univariate [17].…”
Section: Introductionmentioning
confidence: 99%